THE ROLE OF FINANCIAL CONTROL IN REDUCING WASTE OF PUBLIC MONEY THROUGH THE MEDIATING ROLE OF SUSTAINABLE AUDITING (APPLIED RESEARCH) - Lecturer Dr Rebin Tayeb Rashid; Hasan Maytham Kareem; Assist. Prof .Dr. Waad Hadi Abd (Scholar Express Journals, 2023)
The research aims to shed light on the great role provided by financial control in the Iraqi environment, which is represented by the Federal board of supreme audit in the process of preserving financial resources and ensuring that they are not wasted and depleted, and ensuring that it is used efficiently and supporting the growth and stability of the Iraqi economy in a manner that serves sustainable development by activating the mediating role of auditing The sustainable performance carried out by the financial control in evaluating the strategies of government institutions to identify weaknesses and strengths and identify the reasons for failure to reach the performance to the levels expected of them. By conducting an assessment of its current performance as well as evaluating its future vision, and ensuring the validity of data and financial and non-financial information related to the internal, social, economic and institutional activity and their compatibility Regulations and legislations for the protection of natural resources, as well as alerting the management of government institutions in predicting environmental risks and how to address them, limiting and minimizing the consumption of natural resources, and ensuring the optimal use of economic resources by ensuring adherence to regulations and legislations for the protection of natural resources
Keywords: sustainable auditing; public sector auditing; waste of public money